A POTENTIAL STUDY ON DROPLET COMBUSTION PERFORMANCE OF VEGETABLE OIL-CLOVE OIL BLEND - Adhes Gamayel, M.N. Mohammed, Salah Al-Zubaidi , Eddy Yusuf (International Journal of Advanced Science and Technology, 2020)
This study aims to investigate the combustion characteristic of VO-clove oil blend. In this study, two vegetable oils namely; Coconut Oil (CCO) and Kapok Oil (KSO) were blended with clove oil at percentage of 5% on the basis of volume (CCO95C5 and KSO95C5). The combustion of suspended droplet was utilized to show the combustion process and micro-explosion phenomena. The presence of clove oil in fuel blend lead to disruptive burning and more micro-explosion in fuel blend. It’s due to volatility of clove oil that can form bubble easier inside the droplet, ejected, and cause secondary atomization outside the droplet.